Complex variables for scientists and engineers - Paliouras, John D.
The most substantive are the inclusion of many more applications of complex functions theory. A preliminary discussion of applicatios of harmonic functions to physical problems is provided in Chapter 3. The concepts introduced in Chapters 1 and 2 provide sufficient background for this material. The more comprehensive applications presented in Chapter 9, some of which aer extensions of those in Chapter 3, make full use of the theory of complex variables developed in Chapters 4 through 8